Masjid Kasunyatan Banten: Tinjauan Sejarah dan Arsitektur - Saefullah, Asep (Jurnal Lektur Keagamaan, 2018)
Kasunyatan Mosque is one of the historic ancient mosques in Banten. Its existence is less popular than Masjid Agung (the Great Mosque) of Banten in Banten Lama, although both are one of the religious tourism destinations for Indonesian people. At the time of the Sultan (Shaykh) Maulana Yusuf, the second Sultan of the Sultanate of Banten, ruled between 1570-1780 AD, Kasunyatan Mosque is well known as a center of religious and scientific activities other than the Keraton Surosowan and Banten Lama. Across this mosque there is the Tomb of Sultan (Shaykh) Maulana Yusuf which is crowded by the public. This research paper endeavors to describe of how Kasunyatan Mosque in Banten as one of historic places of worship. The research uses historical and architectural approach in understanding and analysing data. Based on this research, it is understood that the Kasunyatan Mosque shows its ancient features in its rectangular shape, solid or massive foundations, thick walls, short mihrab, and pulpits and the Friday sermons in the form of a double-edged sword. Although it has renovated and improved, but the original structure remains visible and its authenticity is maintained. On the southwest side there is also a massive tower, as one of the hallmarks of ancient tower buildings. One of the legacies that is still passed by the present generation is in case  of educative and religious function  of the mosque itself as a center of religious teaching and learning in which the Madrasah Diniyah  (religious School) and regular religious study (majlis taklim) is built and being carried out up to now, besides enabling for other religious activities and ceremonies such as regular religious teaching, the commemoration of Islamic Memorial Days such as Mawlid an-Nabi (Celebrating Prophet Muhammad's Birthday), Isra Mi’raj, Orphans Benefit, and also the haul of Shaykh Maulana Yusuf.Keywords: Kasunyatan, Ancient Mosque, Banten, Maulana Yusuf, Architecture, historical and architectural perspective  Masjid Kasunyatan merupakan salah satu masjid kuno bersejarah di Banten. Keberadaannya kurang popular dibandingkan dengan Masjid Agung Banten di Banten Lama, meskipun dua-duanya merupakan salah satu tujuan wisata religi bagi sebagian masyarakan Indonesia. Pada masa Sultan (Syekh) Maulana Yusuf, sultan kedua dari Kesultanan Banten, berkuasa antara 1570-1780 M., Masjid Kasunyatan dikenal sebagai pusat kegiatan keagamaan dan keilmuan selain di sekitar Keraton Surosowan dan Banten Lama. Di seberang masjid ini terdapat Makan Sultan (Syekh) Maulana Yusuf tersebut yang ramai diziarahi masyarakat. Berdasarkan penelusuran, Masjid Kasunyatan memperlihatkan ciri-ciri kekunoannya pada bentuknya yang segi empat, fondasi padat atau massif, dinding tebal, mihrab pendek, dan mimbar serta tongkat khotib Jum'at berupa pedang bermata dua. Meskipun telah mengalami perbaikan, tetapi struktur aslinya tetap terlihat dan keasliannya dipertahankan. Di sisi sebelah barat daya terdapat juga menara yang massif, sebagai salah satu ciri bangunan menara kuno. Salah satu peninggalannya yang tetap diteruskan oleh generasi sekarang adalah dalam hal pemeranan fungsi pendidikan dan keagamaan, dimana Madrasah Diniyah dan pengajian rutin dibangun dan diselenggarakan, selain untuk pelaksanaan berbagai acara kegiatan keagamaan seperti peringatan hari-hari besar keagamaan, seperti Maulid Nabi Muhammad Saw., Isra Mikraj, Santunan Anak Yatim, dan juga acara haul Syekh Maulana Yusuf.Kata Kunci: Kasunyatan, Masjid Kuno, Banten, Maulana Yusuf, Arsitektur